Why him? - Hamburg, John, 1970-; Franco, James, 1978-; Cranston, Bryan, 1956-; Deutch, Zoey, 1994-; Shapiro, Theodore, 1971- (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2017)
A holiday gathering goes awry when a man finds out that his daughter is planning to get engaged to her wealthy boyfriend.
Originally released as a motion picture in 2016.
Dolby digital 5.1, wide screen 1.85:1.
Features: gag reel, 47 minutes on the can, Why Gustav?, Barb Fleming : America's mom, Lou the entertainer, Richard Blais : twisted chef, deleted scenes, audio commentary, gallery.
Cinematographer, Kris Kachikis ; production designer, Matthew Holt ; editor, William Kerr ; music, Theodore Shapiro.
James Franco, Bryan Cranston, Zoey Deutch, Megan Mullaly, Griffin Gluck.
MPAA rating: R.
Keywords: Fathers and daughters -- Drama; Man-woman relationships -- Drama; Fiction films; Feature films; Comedy films